Uptake of advanced clinical practice roles in the health service in England: Perspectives at the micro level - Francesca Taylor; Vari M. Drennan; Mary Halter; Helen T. Allan; Linda Collins (Elsevier, 2022)
Health care organisations in many countries are developing advanced clinical practitioner roles to address workforce shortages and growing demand for services. Even in countries where advanced practice roles are more established there are low numbers, clustered in a limited range of professions, mostly nursing specialities. Successful implementation of national policies encouraging increased advanced practice roles and from a broader range of professions, requires attention to all levels of the health system. There is a lack of evidence as to the motivation to take-up these roles at the micro, individual actor level. This study explored the motivations important at the micro level in influencing a range of health professionals to undertake advanced practice roles. The study used an interpretive methodology with thematic analysis and was framed by theories of motivational domains in the work environment. Semi-structured interviews were undertaken with eighteen advanced clinical practitioners working in health care organisations in England. The motivators for role take-up were found to be predominantly intrinsic reflecting participants' desires for advancement, both personal and for their profession, and improved efficiency of patient care. Participants described experiencing limited organisational support and sometimes discouragement from other professionals. There is potential for health organisations at the meso level of health care systems to support national growth of advanced practice roles by giving attention to the motivations of diverse health professionals. We propose a new theoretical framework of motivators for advanced clinical practice role uptake at the micro level.